Isolation and Antimicrobial and Antioxidant Evaluation of Bio-Active Compounds from Eriobotrya Japonica Stems - Khaled Nabih Rashed; Monica Butnariu (Tabriz University of Medical Sciences, 2014)
Purpose: The present study was carried out to evaluate antimicrobial and antioxidant activities from Eriobotrya japonica stems as well investigation of its chemical composition. Methods: Methanol 80% extract of Eriobotrya japonica stems was tested for antimicrobial activity against bacterial and fungal strains and for antioxidant activity using oxygen radical absorbance capacity (ORAC) and the trolox equivalent antioxidant capacity (TEAC) assays and also total content of polyphenols with phytochemical analysis of the extract were determined. Results: The results showed that the extract has a significant antimicrobial activity, it inhibited significantly the growth of Candida albicans suggesting that it can be used in the treatment of fungal infections, and it showed no effect on the other bacterial and fungal strains, the extract has a good antioxidant activity, it has shown high values of oxygen radical absorbance capacity and trolox equivalent antioxidant capacity, while it showed a low value of polyphenol content. Phytochemical analysis of the extract showed the presence of carbohydrates, terpenes, tannins and flavonoids, further phytochemical analysis resulted in the isolation and identification of three triterpenic acids, oleanolic, ursolic and corosolic acids and four flavonoids, naringenin, quercetin, kaempferol 3-O-β-glucoside and quercetin 3-O-α-rhamnoside. Conclusion: These results may help to discover new chemical classes of natural antimicrobial antioxidant substances.